Association Between Fatty Liver Index and Incidence of Cataract Surgery in Individuals Aged 50 Years and Older Based on the Korean National Health Insurance Service-Health Screening Cohort (NHIS-HEALS) Data: Longitudinal Retrospective Cohort Study - Yonghwan Kim; Jeongsook Kim; Eoi Jong Seo; Kyung Tae Kim; Jae-woo Lee; Joungyoun Kim; Hee-Taik Kang (JMIR Publications, 2024)
Abstract BackgroundCataract is a leading cause of vision impairment. Obesity-related risk factors, including insulin resistance, increase the risk of cataract. The fatty liver index (FLI) is a biomarker for noninvasive fat layer prediction of nonalcoholic fatty liver disease. The FLI has been used to evaluate the metabolic contribution in other organs besides the eye. However, no study exists on the FLI and eye disease. ObjectiveThis retrospective cohort study for the association between the FLI and incidence of cataract surgery in individuals older than 50 years was designed to show that a higher FLI is associated with an increased incidence of cataract surgery in individuals aged 50 years and older. MethodsThis study was retrospectively designed based on the Korean National Health Insurance Service-Health Screening Cohort (NHIS-HEALS) cohort (median follow-up of 9.8 years). Participants were assigned to 1 of 3 groups based on the FLI: low (FLI<30), intermediate (FLI 30-59), or high (FLI≥60). Kaplan-Meier survival analysis was performed on the cumulative incidence of all-cataract and senile-cataract surgery. Multivariable Cox proportional hazards regression models were used to study the association between the FLI group and cataract surgery after adjusting for potential confounders. ResultsOf the 138,347 included participants, the incidence of cataract surgery was 12.49% (4779/38,274), 13.95% (6680/47,875), and 14.16% (7496/52,930) in the low, intermediate, and high FLI groups, respectively. After adjusting for all confounding factors, hazard ratios (HRs; 95% CIs) in the high FLI group for all-cataract surgery were 1.111 (1.028‐1.199) and 1.184 (1.101‐1.274) in men and women, respectively, when compared with the low FLI group. HRs (95% CIs) in the high FLI group for senile-cataract surgery were 1.106 (1.022‐1.197) and 1.147 (1.065‐1.237) in men and women, respectively, when compared with the low FLI group. The project was conducted between August 2023 and February 2024 without donations from external bodies. ConclusionsIndividuals with a higher FLI had a higher risk of all-cataract surgery. This association was maintained even after limiting the analyses to senile-cataract surgery.